2007
DOI: 10.1016/j.cell.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein S3: A KH Domain Subunit in NF-κB Complexes that Mediates Selective Gene Regulation

Abstract: NF-kappaB is a DNA-binding protein complex that transduces a variety of activating signals from the cytoplasm to specific sets of target genes. To understand the preferential recruitment of NF-kappaB to specific gene regulatory sites, we used NF-kappaB p65 in a tandem affinity purification and mass spectrometry proteomic screen. We identified ribosomal protein S3 (RPS3), a KH domain protein, as a non-Rel subunit of p65 homodimer and p65-p50 heterodimer DNA-binding complexes that synergistically enhances DNA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
439
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(471 citation statements)
references
References 35 publications
21
439
3
1
Order By: Relevance
“…Suppression of IL-8 by CHFR through the inhibition of NF-jB L Kashima et al these two complexes slightly (Figure 3a, lanes 5 and 6), indicating that complex I is a p65 homodimer and complex II is mainly composed of p65/p50 and p65/-c-Rel heterodimers, which is consistent with earlier reports (Sathe et al, 2004;Wan et al, 2007). Therefore, CHFR mainly affected the DNA-binding activity of the p65 homodimer ( Figure 3a, lane 2, complex I).…”
Section: Chfr Downregulates Nf-kb-dependent Transcriptionsupporting
confidence: 92%
“…Suppression of IL-8 by CHFR through the inhibition of NF-jB L Kashima et al these two complexes slightly (Figure 3a, lanes 5 and 6), indicating that complex I is a p65 homodimer and complex II is mainly composed of p65/p50 and p65/-c-Rel heterodimers, which is consistent with earlier reports (Sathe et al, 2004;Wan et al, 2007). Therefore, CHFR mainly affected the DNA-binding activity of the p65 homodimer ( Figure 3a, lane 2, complex I).…”
Section: Chfr Downregulates Nf-kb-dependent Transcriptionsupporting
confidence: 92%
“…In addition, different coactivators have been shown to regulate induction of different subsets of NF-B regulated genes. For example, we have previously shown that IRF3 and Bcl3 function as coactivator for induction of IP-10 but not MCP-1 in response to LPS and TNF␣ stimulation, respectively (22), while others have reported that RPS-3 is critical for induction of a subset of NF-B regulated genes upon TCR stimulation (23). Methylation of p65 may serve as direct or indirect interacting interface for recruiting these coactivators to form an enhanceosome to activate gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…S3 protein is involved in the synthesis of small ribosomal subunit (30S) and in the repair of DNA damage (Kim et al 2005). S3 may also function as a transcription factor (Wan et al 2007). In connection with these functions, this protein may cause an increase in triticale stress tolerance.…”
Section: Discussionmentioning
confidence: 99%